Langerhans Cell Histiocytosis and Frontal Headache - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A most recent case record of the Massachusetts General Hospital involved a clinicopathological presentation of a 15-year-old boy admitted with frontal headache, right retro-orbital pain, and a retro-orbital mass that proved to be a Langerhans' cell histiocytosis involving the right sphenoid sinus and orbit.